Hey, just started this year's calc class and I have a question: If $\displaystyle \dfrac{f(x)g(x)} {h(x)}$ Write the equation of the tangent to $\displaystyle y$ and $\displaystyle x = 3$
Follow Math Help Forum on Facebook and Google+
assuming If $\displaystyle y(x) = \dfrac{f(x)g(x)}{h(x)}$ then the tangent will be $\displaystyle y- y(3) = y'(3)(x-3)$
Thanks for the reply, but can you tell me how you got to that answer?
The equation of a tangent to a function y at x = 3 can be given by $\displaystyle y- y(3) = y'(3)(x-3)$ which is a straight line and comes from the form $\displaystyle y- y_1 = m(x-x_1)$
View Tag Cloud